Concurrent psychiatry for patients enrolled in opioid agonist treatment: a propensity score matched cohort study in Ontario Canada - Kristen A. Morin; Joseph K. Eibl; Joseph M. Caswell; Graham Gauthier; Brian Rush; Christopher Mushquash; Nancy E. Lightfoot; David C. Marsh (BMC, 2019)
Abstract Objective The objective was to characterize the relationship between geography, concurrent psychiatric services, all-cause mortality, and acute health care use for individuals enrolled in Opioid Agonist Treatment, in Ontario, Canada. Methods We conducted a propensity score matching study of patients enrolled in Opioid Agonist Treatment in Ontario for the first time between January 1, 2011, and December 31, 2015. We first compared outcomes between patients who were actively engaged and patients who were not actively engaged in Opioid Agonist Treatment. We created treatment and a control groups on the basis of an individual's access to psychiatric care within an episode of Opioid Agonist Treatment. Relative risk and number needed to treat were calculated to determine the correlation between psychiatric care and health outcomes among patients enrolled in Opioid Agonist Treatment at two time points within an episode of care and for two geographic regions in Ontario (north and south). Results During the first year of Opioid Agonist Treatment, concurrent psychiatric care was associated with a reduction in all-cause mortality in southern Ontario (RR 0.80, 95% CI, 0.73-0.87), a reduction in emergency department visits in both northern and southern Ontario (north: RR = 0.76, 95% CI, 0.72-0.81; south: RR = 0.87, 95% CI, 0.86-0.88), and a reduction in hospitalizations (north: RR = 0.88, 95% CI. 0.82-0.94, south: RR = 0.92, 95% CI, 0.91-0.93). Conclusion Our findings have significant clinical and political implications for health system planning highlighting the need for integrated mental health and addiction services for individuals with Opioid Use Disorder.